The 15 year ankle arthroplasty experience in a university hospital. Issue 2 (February 2022) - Loveday, D.T.; Baskaran, D.; Salmasi, M.Y.; Barrett, M.P.; Smith, G.H.
Highlights: This retrospective study reviewed primary ankle arthroplasty practice over a 15 year period at a single institution. On average 10 primary ankle replacements were performed each year. The outcomes are comparable with international registry data and demonstrate good medium term implant survivorship rates. Abstract: Introduction: The study aim was to review the experience of ankle replacement surgery in a university teaching hospital. Methods: A retrospective review of primary ankle replacements performed between 2005 and 2019 was undertaken. Implant survival and reasons for revision surgery were assessed, along with patient reported outcomes and complications. Results: There were 157 ankle replacements implanted in 140 patients with a mean follow up 7.5 years (range 1.0–14.5). There were 108 Mobility™, 19 Zenith™ and 30 Infinity™ ankle replacements with an overall revision rate of 9.6% at a mean 4.0 years (range 0.1–11.0). Overall survivorship analysis for 5, 10 and 15 years was respectively 92.4%, 89.3% and 86.6%. Discussion: The revision rate was comparable to international registers and aseptic loosening was the commonest reason for revision. This study, in a teaching university hospital with an average of 10 primary ankle replacements each year, highlighted ankle arthroplasty provides good functional outcomes and medium term implant survivorship. This supports the use of ankle arthroplasty within foot and ankle specialist centres achieving appropriate outcomes.